Answer:
See below;
Explanation:
We are given the following;
5 + [ 2 * 2 + 5 ], ⇒ add 2 and 5
5 + [ 2 * 7 ], ⇒ multiply 2 by 7
5 + 14, ⇒ combine like terms
Solution; 19
Now as we can see from the first ⇒ second step the process as to simplify the expression 5 + [ 2 * 2 + 5 ] further, was by adding 2 and 5. Of course by PEDMAS, it would be that multiplication takes place before that of addition, so that it should have been that 2 was multiplied by 2 first!
Solution below;
Steps | |
| 5 + [ 2 * 2 + 5 ] |
X | 5 + [ 2 * 7 ] |
| 5 + 14 |
| 19 |